The problem-based learning model has a significant effect on elementary school students' mathematical concept comprehension skills - Sarila, Anesa Juliati; Fitriani, Andhin Dyas (International Conference on Elementary Education, 2025)
This study aims to determine whether there is a difference in the effect before and after learning using the problem-based learning model in improving students' mathematical concept understanding. This study uses a quantitative approach with a one-group pretest-post-test design to examine the effectiveness of the problem-based learning model in improving students' mathematical concept understanding. Based on the results of the Paired Samples T-Test, a sig. value (2-tailed) = 0.001 was obtained, which is smaller than the significance level α = 0.05. This indicates that H0 is rejected and H1 is accepted, which means that the use of the problem-based learning model has a significant effect on improving the mathematical concept comprehension abilities of fifth-grade students in the subject of fractions. As a whole, the problem-based learning model has been proven to contribute to improving students' mathematical concept comprehension skills.